Kajian Pengaruh Tingkat Cekaman Kekeringan Terhadap Karakteristik Morfologis Kumis Kucing (Orthosiphonristatus (Blume) Miq.) - Nugraheni Hadiyanti; Mariyono Mariyono (Kadiri University, 2019)
Kumis Kucing plant or Cat Whiskers plant (Orthosiphon aristatus (Blume) Miq.) is one of the important medicinal plants in herbal medicine as an antioxidant, antiangiogenic and anticancer agent. Research related to the growth of cat whiskers which is influenced by water content in the soil has not been widely carried out. The purpose of this study was to determine the effect of drought stress levels on the morphological characteristics of cat whiskers. This study used a completely randomized design (CRD), one factor with three replications. Plants that grow upright, rooted in the knuckles but not visible, plant up to 2 m high. Rectangular stem slightly grooved. The drought stress factor consists of 5 levels, namely: 100% field capacity / KL (W0), 50% field capacity (W1), 37.5% field capacity (W2), 25% field capacity (W3) and 12.5% field capacity (W4). The observed data were analyzed by means of analysis of variance and continued with Duncan's multiple distance test (DMRT) at 5% level if the results were significant. The observed data were analyzed by means of analysis of variance and continued with Duncan's multiple distance test (DMRT) at 5% level if the results were significant. The results showed that the level of drought stress affected the morphology of cat whiskers, seen in plant height, leaves and roots. Drought stress 12.5% KL had a negative impact on abnormal growth, small and relatively small leaf size and decreased root dry weight. Cat whiskers are plants that are resistant to drought stress.Kumis kucing (Orthosiphon aristatus (Blume) Miq.) termasuk salah satu tanaman obat penting dalam pengobatan herbal sebagai antioksidan, antiangiogenik dan antikanker. Penelitian terkait pertumbuhan kumis kucing yang dipengaruhi kadar air dalam tanah belum banyak dilakukan. Tujuan dari penelitian adalah untuk mengetahui pengaruh tingkat cekaman kekeringan terhadap karakteristik morfologis kumis kucing. Penelitian ini menggunakan rancangan acak lengkap (RAL), satu faktor dengan tiga kali ulangan. Tanaman yang tumbuh tegak, pada buku-bukunya berakar tetapi tidak tampak nyata, tinggi tanaman sampai 2 m. Batang bersegi empat agak beralur. Faktor tingkat cekaman kekeringan terdiri atas 5 taraf, yaitu: 100% kapasitas lapang/KL (W0), 50% kapasitas lapang (W1), 37.5% kapasitas lapang (W2), 25% kapasitas lapang (W3) dan 12.5% kapasitas lapang (W4). Data hasil pengamatan dianalisis dengan analisis sidik ragam dan dilanjutkan dengan uji jarak berganda Duncan (DMRT) taraf 5% apabila hasil signifikan. Data hasil pengamatan dianalisis dengan analisis sidik ragam dan dilanjutkan dengan uji jarak berganda Duncan (DMRT) taraf 5% apabila hasil signifikan. Hasil penelitian menunjukkan tingkat cekaman kekeringan mempengaruhi morfologi kumis kucing, terlihat pada tinggi tanaman, daun dan akar. Cekaman kekeringan 12.5% KL berdampak buruk pada pertumbuhan yang abnormal, ukuran daun kecil dan relatif sedikit serta penurunan berat kering akar. Kumis kucing termasuk tanaman yang tahan terhadap cekaman kekeringan.